Transformasi Pondok Pesantren (Analisis Dampak Transformasi Sistem Pendidikan Terhadap Penanaman Panca Jiwa Pondok Pesantren Kepada Santri di Provinsi Bengkulu) - A. Suradi (TADRIS: Jurnal Pendidikan Islam, 2017)
Modernization in world missionize and education of Islamic contemporary, do not only altering bases of sosio-kultural and knowledge of eye santri, but also induce at Islamic people as a whole. Equally culture of pesantren always experience of change process as according to its supporter society dynamics. Therefore big changes done/conducted by kyai to institutes of pesantren these days is not represent crosslegged alternative choice of road;street, but represent natural by life values accumulation of pesantren as long as history, without leaving ruh ( typical tradition) of him. Maisonette of Pesantren in inculcating soul/ head pentameter need open also flexible and to demand and growth of world, but remain to provide filter so that his fade-proof elementary value ( Islam teaching). In meaning, maisonette of pesantren do not only external mentransformasi of just him ( target, curriculum, method, management system and management of pesantren) but needing wisely depth mentransformasi also (maisonette soul/ head values of pesantren).